Uji Aktifitas Ekstrak Air Biji Pepaya (Carica papaya L.) Terhadap Pertumbuhan Tanaman Cabai Merah (Capsicum annuum L.) - Yulianty; Salman Farisi; Endang Nurcahyani (BULLET : Jurnal Multidisiplin Ilmu, 2026)
The red chili pepper plant (Capsicum annuum L.) is a type of vegetable. Chili peppers are widely used by the public as a flavorful cooking ingredient. Given the steadily increasing demand for chili peppers, efforts are needed to boost their productivity. One such effort involves applying plant extracts that can promote chili plant growth. Papaya seeds (Carica papaya L.) contain secondary metabolites that can protect plants from pathogen attacks, thereby enhancing chili plant growth. The objectives of this study are to determine the effect of papaya seed water extract on the growth of red chili plants and to identify the optimal concentration of papaya seed water extract for enhancing chili plant growth. The experimental design used was a   Completely Randomized Design (CRD) with papaya seed extract (Carica papaya L.) as the treatment, consisting of four concentrations: 0%, 1%, 2%, and 3%, with six replicates. The parameters observed were the time of radicle emergence, plant height, fresh weight, and dry weight. The data were analyzed using analysis of variance (ANOVA) and the BNJ test at the 5% level. The results showed that the best concentration was P4 (3%) for increasing radicula emergence, plant height, fresh weight, and dry weight.